Analysis of Nutritional Status in Toddlers and Malaria Incidence - Christina Tien Popang; Yuni Subhi Isnaini; Mulyanti Mulyanti; Ester Ester (GLOBAL HEALTH SCIENCE GROUP, 2024)
Poor nutritional status in toddlers and the high incidence of malaria are two major health issues that continue to be significant challenges in Indonesia, particularly in tropical regions such as Papua. Children's health is heavily influenced by these two factors, where malnutrition can weaken the immune system, making them more vulnerable to infectious diseases like malaria. Toddlers with poor nutritional status, such as stunting and undernutrition, are more likely to contract malaria, which in turn worsens their health condition and can lead to various long-term complications. This study aims to explore the relationship between the nutritional status of toddlers and malaria incidence at Kimi Health Center in Nabire Regency in 2024. Using a descriptive-analytic approach with a cross-sectional design, The population of this study consists of 804 toddlers at Kimi Health Center, with 118 samples selected using purposive sampling. The instrument used in this study is a standardized questionnaire, which includes questions about the respondents' characteristics and factual information regarding their condition, as well as the results of laboratory malaria tests with positive results, the study will analyze data using the Kendall Tau test. The findings highlight that poor nutritional status, including conditions like Protein-Energy Malnutrition (PEM), increases the risk and severity of malaria, impairing the immune response and exacerbating complications such as anemia. Conversely, excess nutrition, such as obesity, can also compromise immunity, increasing malaria risk. Nutrient deficiencies, such as in iron, vitamin A, and zinc, further affect immune function and vulnerability to malaria. Improving nutritional status is crucial for reducing the risk and impact of malaria, particularly in endemic areas like Nabire.